Spatial Analysis in Population and Environment: Application to the study of dengue in Caraguatatuba, São Paulo, in 2013 (Revista Espinhaço, 2014)
In this article, our goal was to demonstrate the potential of using the tools of GIS and spatial analysis in discussions about the interrelationships between population and environmental dynamics. Therefore, we observed the influence of the distribution of environmental sanitation services in the dispersion of dengue cases in the city of Caraguatatuba in the state of São Paulo (Brazil), in 2013. Our methodology included the distribution of information from the 2010 Population Census on regular grids, performing then a cluster analysis and the Local Moran Index. Our results indicate that although dengue is a multifactorial disease, the GIS tools and spatial analysis can greatly enhance the understanding of the role played by some of these causal factors through its isolation from the others.
Keywords: spatial analysis; cluster analysis; local moran index; dengue; caraguatatuba